2021
DOI: 10.3390/nu13082583
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia and Vitamin D Deficiency in Children with Inflammatory Bowel Diseases and Lactose Intolerance

Abstract: Background: A diet restricted in dairy products can cause calcium and vitamin D deficiency and, secondarily, lead to malnutrition and low bone mass. The aim of the study was to determine the incidence hypocalcemia and vitamin D deficiency in children with inflammatory bowel diseases and lactose intolerance (LI). Material and Methods: A total of 107 patients were enrolled to the study (mean age 14.07 ± 3.58 years; 46.7% boys): 43 with Crohn’s disease (CD), 31 with ulcerative colitis (UC), and 33 with functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
8
0
2
Order By: Relevance
“…Data from studies analyzing this association in IBD children require further studies due to the small sample size [ 31 ], although some researchers suggest a higher prevalence of vitamin D deficiency in patients with Crohn’s disease with upper gastrointestinal tract involvement [ 32 , 38 ]. In the literature it is suggested that resection of the small intestine may be a risk factor for vitamin D deficiency [ 39 , 40 ]. In our study, we did not confirm that hypothesis, and other researchers—mainly in pediatric studies—did not show such a correlation as well [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from studies analyzing this association in IBD children require further studies due to the small sample size [ 31 ], although some researchers suggest a higher prevalence of vitamin D deficiency in patients with Crohn’s disease with upper gastrointestinal tract involvement [ 32 , 38 ]. In the literature it is suggested that resection of the small intestine may be a risk factor for vitamin D deficiency [ 39 , 40 ]. In our study, we did not confirm that hypothesis, and other researchers—mainly in pediatric studies—did not show such a correlation as well [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…IBD patients often avoid dairy products because they are afraid of symptoms of lactose intolerance [ 39 ]. Consequently, in addition to the low dose of vitamin D, they do not provide the body with the right amount of calcium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Традиционно наше представление об обеспеченности витамином D детей было по сравнению со взрослыми было более оптимистичным в связи с большей приверженностью детей к приему профилактических доз холекальциферола [1,2]. Однако недавние исследования с включением различных по величине когорт пациентов свидетельствуют о низкой обеспеченности 25(ОН)D как среди практически здоровых детей вне зависимости от региона их проживания, так и среди детей с различными отклонениями в состоянии здоровья [3][4][5][6][7][8][9][10][11][12][13]. Основная проблема исследований по обеспеченности витамином D заключается в отсутствии комплексного подхода, то есть динамической оценки 25(ОН)D в течение всего периода детства и в различные сезоны года.…”
Section: актуальностьunclassified
“…The same study showed that children with CD or UC were statistically more likely to develop hypocalcemia. Due to the occurrence of malabsorption disorders and increased loss in the gastrointestinal tract, this group of patients has a greater need for supplementation, which, despite its safety and general tolerance, is not always sufficient [ 46 ]. However, maintaining the 25-OHD concentration above 30 ng/mL may improve calcium absorption and ensure an adequate range of parathyroid hormone (PTH) [ 47 ].…”
Section: Introductionmentioning
confidence: 99%